2018
DOI: 10.1111/jvh.12865
|View full text |Cite
|
Sign up to set email alerts
|

Increased oestradiol in hepatitis E virus‐infected pregnant women promotes viral replication

Abstract: Hepatitis E virus (HEV) infection causes subclinical diseases, leading to high mortality (>25%) in pregnant women. HEV replication is aggressively escalated in pregnant women, especially in the third trimester of pregnancy. Oestrogen plays an important role in pregnancy. However, the pathogenesis of HEV in pregnant women or immunosuppressive pregnant women (such as HIV-infected or organ-transplanted pregnant women) remains unclear. We investigated the role of oestradiol in HEV infection in a cell culture syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 32 publications
4
50
0
Order By: Relevance
“…The successful establishment provided a valuable chance to explore the underlying mechanism of HEV infection. In this study, higher viral titers were detected in the fecal and blood samples of pregnant rhesus macaques than in non-pregnant rhesus macaque; this result was consistent with the classical clinical symptoms of HEV infection in pregnant women 45 . In our previous study, we confirmed estrogen-promoting HEV replication in cells when estrogen analogs are supplied (17β-estradiol or diethylstilbestrol) 45 .…”
Section: Discussionsupporting
confidence: 87%
“…The successful establishment provided a valuable chance to explore the underlying mechanism of HEV infection. In this study, higher viral titers were detected in the fecal and blood samples of pregnant rhesus macaques than in non-pregnant rhesus macaque; this result was consistent with the classical clinical symptoms of HEV infection in pregnant women 45 . In our previous study, we confirmed estrogen-promoting HEV replication in cells when estrogen analogs are supplied (17β-estradiol or diethylstilbestrol) 45 .…”
Section: Discussionsupporting
confidence: 87%
“…The levels of the three hormonal factors were found to be higher in HEV-positive pregnant FHF patients than in HEV-negative patients or controls [104]. Increased estradiol in the serum of HEV-infected pregnant women promoted viral replication [114,115], which may be associated with poor outcomes [86]. In addition, a high level of estrogen was found to be related to preterm delivery, low birth weight infants and fetal mortality through placental dysfunction in pregnant women with HEV infection [116].…”
Section: Hormonal Factorsmentioning
confidence: 99%
“…(288) Proposed factors contributing to risk in pregnancy include HEV genotype 1 (with varying replication efficiency at the maternal-fetal placenta interface), (289,290) folate or other nutritional deficiencies, (291) and immunologic changes in pregnancy. (292) Acute HEV is responsible for an estimated 3,000 stillbirths worldwide annually, (293) with fetal and neonatal mortality rates likely influenced by the severity of maternal illness. A systematic review reported the median fetal and neonatal case fatality rate of 33% (interquartile range [IQR], 19%-37%) and 8% (IQR, 3%-20%), respectively.…”
Section: Hepatitis Ementioning
confidence: 99%